Accuracy Evaluation of Access Cavity Preparation between Guided Endodontics and Conventional Technique - Singh, Santosh Kumar; Mishra, Pankaj; Yadav, Siddhi; Dubey, Priyanka; Pandey, Suchi; Sitlani, Muskan; Di Blasio, Marco; Cicciù, Marco; Minervini, Giuseppe (European Journal of General Dentistry, 2025)
Objective The accuracy of endodontic access cavity preparation is crucial for the success of root canal treatment. This study aimed to compare the precision and efficiency of Guided Endodontics (GE) versus conventional techniques in locating and navigating root canals, examining the deviation from planned to performed procedures, and assessing the procedural time differences between the two methods.Materials and Methods We utilized six sets of mandibular and maxillary jaws, each with 10 extracted single-rooted teeth, for our study. The teeth were divided into two groups for GE and conventional preparation. Preoperative CBCT and intraoral scans were used to facilitate virtual planning for GE, while conventional techniques relied on periapical radiographs. Two trained endodontists performed access cavity preparations on both groups, with deviations from the planned to the actual cavity and procedural times recorded meticulously.Results Out of 60 teeth accessed, GE achieved a 100% canal detection rate, whereas the conventional technique identified 70% of the canals. The procedural time was significantly less for GE. Deviation analysis showed a linear discrepancy in the coronal region of 0.164 ± 0.190 mm and 0.254 ± 0.223 mm in the apical region for the first operator, with the second operator presenting similar deviations. Angular deviations were nearly identical between both operators.Conclusion GE demonstrated superior accuracy in canal detection with less procedural time compared to the conventional technique. Although the difference in canal detection rate was not statistically significant, the reductions in time and linear deviation suggest that GE may offer a more precise and efficient approach to access cavity preparation.
Keywords: access cavity preparation; angular deviations; canal detection; cone-beam computed tomography; guided endodontics; linear deviation